Motivational cultural intelligence and expatriate talent adjustment: an exploratory study of the moderation effects of cultural distance - Song, Hemin; Varma, Arup; Zhang Zhang, Yingying (International journal of human resource management, 2023)
The purpose of this paper is to explore the relationship between motivational cultural intelligence and cultural adjustment of expatriate talent through the lens of cultural distance. The rapid development of MNCs from emerging markets and the corresponding increase in the need for expatriates makes it imperative that scholars examine this subject from numerous critical angles. Drawing on data from 242 Chinese expatriates based in 25 different countries/regions, we employ multilevel analyses to test the research hypotheses related to expatriate talent management. The results of this exploratory study confirm that motivational cultural intelligence has a positive and significant effect on cultural adjustment: work adjustment, general adjustment and interaction adjustment respectively, and cultural distance has a negatively moderating role between motivational cultural intelligence and work adjustment of expatriate talent. This paper helps to expand our understanding of the field of global talent management and the importance of motivational cultural intelligence and cultural distance on expatriate talent.